Ethnobotanical survey of medicinal plants growing in the region of "Oulad Daoud Zkhanine" (Nador Province), in Northeastern Morocco - Hayat, Jaadan; Mustapha, Akodad; Abdelmajid, Moumen; Mourad, Baghour; Ali, Skalli; Said, Ezrari; Saadia, Belmalha (Ethnobotany Research and Applications, 2020)
Background: Medicinal plants occupy a central place in the treatment of various diseases in Morocco’s rural communities. But, complete ethnobotanical studies conducted on those communities medicinal plants are few, thus the present study was carried out in the commune of Oulad Daoud Zkhanine in Northeastern of Morocco in order to establish a catalogue of the various medicinal plants used by the local population for therapeutic purposes. Methods: A non sampling method was conducted to choose the population living in and around this area, herbalists, traditional practitioners and healers. This study targeted 210 people, including 33.3% men and 66.7% women, aged from 18 to 81 years. Surveys and interviews were conducted in Tharifit (local Berber language), between January 2018 to February 2019. Results: This Ethnobotanical study reported 44 medicinal plant species belonging to 28 families, the most abundant of which are Lamiaceae (15.6 %). This study revealed also that leaves are the most commonly used parts of the plant (54.8 %) and that the most remedies are prepared as decoction (48.1 %). Digestive disorders rank first among the diseases treated by these plants with a rate of 51.9%. Conclusion: The present study show that the traditional use of medicinal plants still persists in the Oulad Daoud Zkhanine commune, despite the revolution in medical technology. Keywords: Ethno-botanical, plants, Oulad Daoud Zkhanine, Nador, Morocco